2002
DOI: 10.1074/jbc.m108433200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Duplin, a β-Catenin-binding Protein, Is Essential for Its Inhibitory Activity on the Wnt Signaling Pathway

Abstract: Duplin binds to ␤-catenin and inhibits the Wnt signaling pathway, thereby leading to repression of the ␤-catenin-mediated transactivation and Xenopus axis formation. To find an additional function of Duplin, yeast two-hybrid screening was carried out. Importin ␣ was isolated as a binding protein of Duplin. Importin ␣ bound directly to basic amino acid clusters of Duplin. Although Duplin was present in the nucleus, deletion of the basic amino acid clusters (Duplin ⌬500 -584 ) retained Duplin in the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 60 publications
4
19
1
Order By: Relevance
“…Contrary to our findings, previously published reports identified Chd8 as a negative regulator of canonical-Wnt/β-catenin signaling 10,13,36 . It is worth noting that these earlier studies were conducted in non-neuronal cells, suggesting that Chd8 could play cell-type specific roles in regulating Wnt signaling.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, previously published reports identified Chd8 as a negative regulator of canonical-Wnt/β-catenin signaling 10,13,36 . It is worth noting that these earlier studies were conducted in non-neuronal cells, suggesting that Chd8 could play cell-type specific roles in regulating Wnt signaling.…”
Section: Resultscontrasting
confidence: 99%
“…It was initially identified as a binding partner and negative regulator of β-catenin signaling and was shown to be enriched in the promoters of transcriptionally active genes 1013 . Homozygous deletion of Chd8 in mice results in early embryonic lethality resulting from massive apoptosis 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of this fragment led to the conclusion that Duplin is a negative regulator of the Wnt signaling pathway and functions by blocking the binding of ␤-catenin to TCF (61). However, further studies also indicated that Duplin could attenuate the Wnt signaling pathway downstream of ␤-catenin target genes (38). Bioinformatic analysis suggests that Duplin arose from an improper splicing event, and no evidence for the existence of a human counterpart can be found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Since MITF is a candidate SUMO-target protein, the inhibitory effect of PIAS3 on MITF is presumably also linked to SUMO modification [47]. Another PIAS target in the Wnt pathway is duplin, a nuclear inhibitor of b-catenin [48]. Duplin has also been reported to bind to PIAS.…”
Section: Wnt Signallingmentioning
confidence: 97%